Application of Exploration of Geometry Shapes with Various Media to Improve Learning Outcomes Masjid Raya Islamic Kindergarten students - Zaimar Zaimar (STKIP Rokania Pasir Pangaraian, 2023)
The goal to be achieved in this research is to improve the learning outcomes of Islamic Kindergarten students at the Grand Mosque by exploring geometric shapes. The research will be conducted in two cycles in August 2021 and September 2021. The research tool uses Learning Outcomes tables and Observation tables. The learning achievement table is used to record quantitative data on student learning outcomes before and after the cycle. Observation sheets are used to record qualitative data in the form of observations of student participation in learning activities before and after the cycle. Data analysis used descriptive analysis techniques. Quantitative data in the Learning Outcomes table is processed using percentage analysis. Qualitative data from the observation table, categorized according to the aspects that are used as the focus of analysis. Quantitative and qualitative data are then linked as a basis for describing the successful application of various learning media which is marked by an increase in learning outcomes of geometric shapes and in line with changes in engagement (student behavior in the classroom). Quantitative data collection standard performance indicators show that students in the above categories are getting more and more geometric shape learning outcomes, indicating an increase in learning quality standards. Performance indicators from qualitative data determined that increased student engagement and positive attitudes, both qualitatively and quantitatively, were indicators of increased active learning from cycle to cycle. The results showed that student learning outcomes increased from cycle to cycle. The standard of student engagement increases each cycle along with the increase in student learning outcomes. This was marked by an increase in the percentage of student learning outcomes that obtained criteria scores 4 and 5. After the first cycle it rose very sharply, students who scored 4 and 5 reached 2.6 % ( 9 children) and 24 % ( 8 children) at the time before cycle. A score of 5 was 7 people ( 21 %), who got a score of 4 were 9 students (2 6 %) and who got a score of 3 were 18 students (53 %) in cycle I and increased to as many as 25 students got a score of 5 ( 74 %) ) and as many as 9 students get a score of 4 (2 6 %) in cycle II